PPAR-{alpha} ROLE IN OBESITY-DIABETES IN MICE - ATTAKPA, S. EUGÈNE; SEZAN, ALPHONSE; Seri, Bialli (My University, 2013)
Background. Peroxisome proliferator–activated receptors (PPAR)α and γ are ligand-activated transcription factors and members of the nuclear hor-mone receptor superfamily that regulate the metabolism of glucose and li-pids. Aim. This study investigated the effects of PPARα deficiency on body weight in wild type and PPAR-αnull mice. Materials and methods. The study was performed on male wild type (WT) mice and homozygous PPAR-αnull (PPARα-knockout) mice of C57BL/6J ge-netic background. The mRNA expression was quantitatively analyzed by the real time of polymerase chain reaction (RTPCR). Liver TG content was measured by using a commercially available kit. Serum triglyceride (TG) content was measured using enzymatic methods. Serum insulin was deter-mined using an ELISA kit. Serum glucose was determined by the glucose oxidase method using a glucose analyser. Results. Compared with WT, PPAR-αnull mice had high relative adipose tis-sue weight. These mice exhibited high adiposity state. PPAR-αnull mice also expressed high adiponectin and leptin mRNA levels compared to wild type animals. The PPAR-αnull mice had significantly higher body weight than WT. Hepatic TG and FFA were higher in PPAR- αnull mice as compared to WT animals. PPAR-αnull mice had a high accumulation of TG and FFA in the plasma. Serum insulin concentrations and its pancreatic mRNA transcripts were downregulated in PPAR-αnull mice, suggesting that PPARα gene dele-tion contributes to low insulin gene transcription. We have reported that PPARα deficiency leads to hypoglycaemia in mice. Conclusion. It is suggested a role of PPARα in obesity-diabetes in mice by studying PPARα-knockout mice.
Keywords: PPARα; Insulin; adiponectin mRNA; leptin mRNA; hypoglycaemia; free fatty acids; triglyceride.